Management of Uterine Inversion: An Obstetric Catastrophe - Habib, Asma (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Not available DOI: http://dx.doi.org/10.3329/bjog.v25i2.13744 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(2) : 77-84